Prediction the Manning’s Coefficient by HEC-RAS for Al-Meshkab River - Hadi Sahib, Jumana; ., .; ., . (International Journal of Engineering and Technology, 2018)
The Manning's coefficient represents the roughness characteristics of the channel, which directly affects open channel calculations. In this study, it been calculated which estimation of Manning's coefficient (n) by some of the collected data .The remaining data is utilized for check of the model testing with actual data, which is called verification. The model was adopted by a one-dimensional mathematical by using the HEC-RAS program. The region was studied at the upstream of the Al-Meshkab Barrage, where data were collected in 2010. The coefficient of Manning's roughness (n) is given well agreement between computed data and observed data at n equal to (0.031) for Al-Meshkab River. Â Â Â